HUBUGAN ANTARA DUKUNGAN KELUARGA DAN LINGKUNGAN FISIK DENGAN PRAKTIK PROTEKSI PAPARAN ASAP ROKOK PADA BALITA OLEH KEPALA RUMAH TANGGA (Studi di Wilayah Kelurahan Tandang Kota Semarang) - Muslim Muslim; Laksmono Widagdo; Ratih Indraswari (Jurnal Kesehatan Masyarakat (Undip), 2019)
Exposure of cigarette smoke will cause health problems, not only for active smokers but also for passive smokers. Smoking in the home is a risk behavior for the health of family members, especially toddlers because in the toddler's age the organs in a toddler's body are developing. For this reason, there is a need for the role of the head of the household, in this case, to provide protection toddlers so that they are not exposed to cigarette smoke from themselves and other people's cigarette smoke.This study aims to analyze the family support and physical environment with the practice of protecting exposure to cigarette smoke in infants by the head of the household in the Tandang Village, Semarang City.The method used in this study is quantitative with a cross-sectional approach. The population in this study were 1,042 male parents of toddlers who were active smokers, which then determined a sample of 101 people through the Probability Sampling Stratified Random Sampling technique. This study uses univariate and bivariate analysis using the Chi-Square test.The results showed that there was a relationship between family support (p = 0.031) and physical environment (p = 0.032) with the practice of protection of the head of the household. The need for increasing parents' knowledge of the dangers that can be caused by cigarette smoke to infants and increasing awareness of parents in preventing exposure to cigarette smoke in infants.